2016
DOI: 10.5194/acp-16-9935-2016
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of in situ NDIR and column FTIR measurements of CO<sub>2</sub> at Jungfraujoch

Abstract: Abstract. We compare two CO2 time series measured at the High Alpine Research Station Jungfraujoch, Switzerland (3580 m a.s.l.), in the period from 2005 to 2013 with an in situ surface measurement system using a nondispersive infrared analyzer (NDIR) and a ground-based remote sensing system using solar absorption Fourier transform infrared (FTIR) spectrometry. Although the two data sets show an absolute shift of about 13 ppm, the slopes of the annual CO2 increase are in good agreement within their uncertaintie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…This may be explained by the fact that our TCCON column observations were calibrated to World Meteorological Organization (WMO) scale, while the cited column observations were not. Furthermore, the column observations by Schibig et al [16], showing a difference of 13 ppm with respect to surface measurements at the Jungfraujoch, were performed in the mid-infrared, not in the near-infrared as our TCCON observations. In this context, we note that Buschmann et al [30] showed that the sensitivity of mid-infrared CO 2 column retrievals is a factor of two lower in the troposphere compared to TCCON-type near-infrared retrievals used in our study.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…This may be explained by the fact that our TCCON column observations were calibrated to World Meteorological Organization (WMO) scale, while the cited column observations were not. Furthermore, the column observations by Schibig et al [16], showing a difference of 13 ppm with respect to surface measurements at the Jungfraujoch, were performed in the mid-infrared, not in the near-infrared as our TCCON observations. In this context, we note that Buschmann et al [30] showed that the sensitivity of mid-infrared CO 2 column retrievals is a factor of two lower in the troposphere compared to TCCON-type near-infrared retrievals used in our study.…”
Section: Discussionmentioning
confidence: 48%
“…This higher value is assumed to be due to the global averaging effect, while our results show a more specific signature of the Zugspitze region. Equally, Schibig et al [16] reported that correlations between the FTIR and in-situ NDIR measurements, both with and without seasonality, reached 0.82 as well.…”
Section: Seasonalitymentioning
confidence: 94%
“…After we changed from pure CO 2 to 6 vol % CO 2 mixed with N 2 , we went a step further to use dry compressed air that had a CO 2 concentration of 380–420 ppm . As we know that the rate of reaction increases at higher temperatures from the DSC results, a temperature between 60 and 70 °C was selected.…”
Section: Resultsmentioning
confidence: 99%
“…As CO is usually co-emitted with CO 2 during incomplete combustion of fossil and other fuels, we have also computed a tracer ratio designated as ΔCO/ΔCO 2 from the enhancements in the in-situ measured CO and CO 2 mixing ratios over the Jungfraujoch background (Oney et al, 2016, In review). CO 2bg values were obtained by applying the robust extraction of baseline signal (REBS) statistical method to the continuous CO 2 measurements at the high altitude site Jungfraujoch (Schibig et al, 2016) with a band width of 60 days. Note that while R CO strictly refers to the ratio of ΔCO to fossil fuel CO 2 emissions, the ΔCO/ΔCO 2 ratio can be influenced by biospheric contribution as well as CO 2 emissions from non-fossil sources such as biofuels and biomass burning.…”
Section: Calculation Of R Co δCo/δco 2 and High Resolution Co 2ffmentioning
confidence: 99%